Environmental, social and governance (ESG) and innovation in the construction sector: Systematic Literature Review - Cruz, Pedro Lucas; Ávila, Lucas Veiga; Pimenta Dinis, Maria Alzira; Baggio, Daniel Knebel (Revista de Administração da UFSM, 2023)
Purpose – To analyze the evolution of Environmental, Social and Governance (ESG) and innovation in the civil construction industry, focusing on innovative and sustainable practices, as well as ways of measuring the level of construction companies in these themes. Design/methodology/approach – A Systematic Literature Review approach was used. The Web of Science and Elsevier Scopus Databases, from 2017 to 2022, were used for data collection, based on a set of keywords and Boolean operators ("sustainable development" & "framework" & "measurement" & "environment”). Using the Zotero Software, 488 papers were classified and organized according to the publication date, main content, proposals for sustainable and innovative tools and techniques. The papers were analyzed in the VOSviewer Software. Findings – There is an Asian predominance in the volume of publications and networks of strong connections in clusters by countries. The authors tend to look for papers from the same region as a reference, going against the concept of globalization of ESG and innovation themes and the condition of replicability of practices. Among the exemplified practices, there are replicable models and initiatives, as well as incipient innovative construction materials and methods in search of consolidation. Originality/value – Amid the current and growing discussion about innovation and ESG in organizations, it is noted that the civil construction sector still lacks better performances in these themes. This paper aims to contribute to the advancement of the discussion in the sector, bringing together works found in recent literature.